Introduction of moisture-holding polymer «Aquasorb» during landing wood-shrubby and fruit plants in the arid conditions of Kazakhstan - Vdovina, Т.А.; Vinokurov, А.А.; Lagus, О.А.; Isakova, Е.А. (KSU publ., 2018)
The increasing deficiency of water resources in arid conditions of Kazakhstan forces to find the new directions of use of water-conservation technologies. One of perspective alternative technologies is use of waterabsorbing synthetic polymers. In article norms and ways of introduction of water absorbent «Aquasorb» during landing wood and shrubby fruit plants in droughty territories of the Republic of Kazakhstan are considered. The aim of method consists in definition of an optimum way of absorbent during landing wood cultures for more effective use of useful properties of this preparation. Field and laboratory researches on light brown loamy soils for this purpose are conducted. As the results of experiences use of the combined method, when on a bottom of a landing hole saturated water polymer is brought is recommended, and the volume of the taken- out soil is added the dry preparation saturated later with water before formation of gel particles. For the tree species landed with the soil it is recommended to do punctures in the created earth lump in which dry polymer at addition of saturated absorbent is fallen asleep for a bottom of a landing hole. This way simplifies entering of polymer into a soil substratum during landing wood cultures and allows distributing evenly in a radical zone of plants..
Қазақстанның аридті жағдайында ағаш-бұта жəне жеміс өсімдіктерін отырғызу кезінде «Aquasorb» ылғал ұстайтын полимерін енгізу
Внесение влагоудерживающего полимера «Aquasorb» при посадке древесно-кустарниковых и плодовых растений в аридных условиях Казахстана
Keywords: hydro gel; soil; moisture; wood and shrubby cultures; fruit plants